Advances in Soft and Hard Computing - Pejaś, Jerzy; El Fray, Imed; Hyla, Tomasz; Kacprzyk, Janusz (Advances in Intelligent Systems and Computing, 2019)
The book presents a collection of carefully selected, peer-reviewed papers from the 21st International Multi-Conference on Advanced Computer Systems 2018 (ACS 2018), which was held in Międzyzdroje, Poland on September 24th-26th, 2018. The goal of the ACS 2018 was to bring artificial intelligence, software technologies, biometrics, IT security and distance learning researchers in contact with the ACS community, and to give ACS attendees the opportunity to exchange notes on the latest advances in these areas of interest. The primary focus of the book is on high-quality, original and unpublished research, case studies, and implementation experiences. All of the respective papers are of practical relevance to the construction, evaluation, application or operation of advanced systems. The topics addressed are divided into five major groups: artificial intelligence, software technologies, information technology security, multimedia systems, and information system design.